2019
DOI: 10.1007/s11060-019-03209-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after craniotomy for resection of craniopharyngiomas in adults: analysis of the National Surgical Quality Improvement Program (NSQIP)

Abstract: Purpose Craniopharyngiomas occur in suprasellar locations that pose challenges for surgical management. This study evaluates the incidence of complications following craniotomy for craniopharyngioma in adults and investigates risk factors for these complications. Methods Patients who underwent craniotomy for excision of craniopharyngioma were identified from the 2005-2016 American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP). Incidence of 30-day postoperative complications was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Typically, the surgical outcome is closely associated with the extent of resection (3,7,22). Reports showed that the extent of resection is an independent predictor of tumor recurrence (7,16,17,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the surgical outcome is closely associated with the extent of resection (3,7,22). Reports showed that the extent of resection is an independent predictor of tumor recurrence (7,16,17,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Craniotomy was thought to be the optimal surgical modality for the treatment of ONB patients with intracranial involvement. However, craniotomy may lead to complications such as cerebrospinal fluid leak, meningitis, brain abscess, mental status changes, hematoma, and hemorrhage (9)(10)(11). While craniotomy can achieve adequate access to the invaded portion of the anterior skull base in advanced ONB, the transnasal approach should be used in selective patients on a case-by-case basis with a careful review of imaging and patient's anatomy (12).…”
Section: Discussionmentioning
confidence: 99%
“…e middle column shows significant bivariate relationships between the pathological features displayed in the adjacent panels in the same row and the surgical outcome, in a cohort of 200 CP patients treated in the magnetic resonance imaging (MRI) era (P < 0.001). [5,7] (a) Brain specimen of a CP (t) without hypothalamic involvement. Note the tumor is expanding in the sellar and suprasellar compartments, below an intact third ventricle floor (3VF).…”
Section: Surgical Neurology Internationalmentioning
confidence: 99%
“…In this context, attention should be drawn here to a recent study by Rock et al, from the Department of Neurosurgery at Virginia Commonwealth University in Richmond, VA, USA, that analyzed the incidence of surgical complications in 143 CPs operated on in different centers in the United States. [7] is article focused on the set of information related to the occurrence of intra-and/or postoperative complications in CP surgery, a matter of special concern at a time when unsatisfactory surgical results are not generally the subject of open discussion. As an initial approach to this subject, Rock et al analyzed common unsatisfactory neurosurgical results, such as unexpectedly prolonged ventilation, reoperation, and/or readmission within the 1 st month following surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation